Finding the Optimal Solution to the Problem of Conditional Optimization on the Graph of the set of Placements - Koliechkina, L.M.; Nahirna, A.M. (Control systems & computers, 2020)
An optimization problem on a combinatorial set of partial permutations with additional constraints is formulated in the paper. An algorithm for solving this type of problem is considered, which consists of four steps. The algorithm lies in constructing a graph of a set of partial permutations to find the optimal solution. An example of a practical implementation of the presented algorithm is given.